Mechanistic Insights into the Pre‐Lithiation of Silicon/Graphite Negative Electrodes in "Dry State" and After Electrolyte Addition Using Passivated Lithium Metal Powder. Issue 25 (13th May 2021) - Bärmann, Peer; Mohrhardt, Marvin; Frerichs, Joop Enno; Helling, Malina; Kolesnikov, Aleksei; Klabunde, Sina; Nowak, Sascha; Hansen, Michael Ryan; Winter, Martin; Placke, Tobias
Abstract: Because of its high specific capacity, silicon is regarded as the most promising candidate to be incrementally added to graphite‐based negative electrodes in lithium‐ion batteries. However, silicon suffers from significant volume changes upon (de‐)lithiation leading to continuous re‐formation of the solid electrolyte interphase (SEI) and ongoing active lithium losses. One prominent approach to compensate for active lithium losses is pre‐lithiation. Here, the "contact pre‐lithiation" of silicon/graphite (Si/Gr) negative electrodes in direct contact with passivated Li metal powder (PLMP) is studied, focusing on the pre‐lithiation mechanism in "dry state" and after electrolyte addition. PLMP is pressed onto the electrode surface to precisely adjust the degree of pre‐lithiation (25%, 50%, and 75%). By in situ XRD and ex situ 7 Li NMR studies, it is proven that significant lithiation of Si/Gr electrodes occurs by direct contact to Li metal, that is, without electrolyte. After electrolyte addition, de‐lithiation of silicon and graphite is confirmed, resulting in SEI formation. The amount of Li metal highly impacts the presence and durability of the Li x C and Li x Si phases. Finally, the challenges for homogeneous pre‐lithiation and SEI formation are identified, and the impact of electrolyte addition is assessed by analysis of the lateral and in‐depth lithium distribution within the Si/Gr electrode. Abstract : Continuous re‐formation of the solid electrolyte interphase and ongoing active lithium losses of Si‐based materials are a serious challenge for implementing significant amounts of Si in state‐of‐the‐art graphite negative electrodes. Pre‐lithiation via Li metal powder is investigated electrochemically and analytically toward the lithiated phases and lithium distribution by revealing the impact of the electrolyte on the overall pre‐lithiation behavior.